Pelatihan Penyampaian Kata Sambutan Bagi Pengajian Remaja Nurussalam Aek Badak - Eli Marlina Harahap (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2022)
The training for delivering the speech text was carried out because self-confidence among PRN youth still needed to be motivated. The PKM method this time offers training implementation that starts with delivering material and practicing with practice. Manuscripts that have been written by each participant are given a section with a slash (/) as a pause marker. This activity is a continuation of the speech writing training which was carried out on the same object. The expected result is that the skills of PRN youth in honing their public speaking skills can be further improved. In this way, PRN youth can take more part in their environment in various social events.